2016
DOI: 10.1089/ten.teb.2015.0167
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Influences on Endothelial to Mesenchymal Transition in Developing Implanted Cardiovascular Tissue-Engineered Grafts

Abstract: Tissue-engineered grafts for cardiovascular structures experience biochemical stimuli and mechanical forces that influence tissue development after implantation such as the immunological response, oxidative stress, hemodynamic shear stress, and mechanical strain. Endothelial cells are a cell source of major interest in vascular tissue engineering because of their ability to form a luminal antithrombotic monolayer. In addition, through their ability to undergo endothelial to mesenchymal transition (EndMT), endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 111 publications
1
19
0
Order By: Relevance
“…These data show that the effects of LOXL2 on EC migration and sprouting do not depend on LOXL2mediated enzymatic crosslinking of ECM components, but rather point toward a mechanism involving LOXL2-mediated intracellular signaling. 3.3 | LOXL2 is required but not sufficient to induce EndMT Given the known stimulatory effects of EndMT on angiogenesis (Muylaert et al, 2015;van Meeteren & ten Dijke, 2012) and the reported dominant role of LOXL2 in the regulation of EMT , we hypothesized that the observed results may be explained by a similar regulatory function of LOXL2 in EndMT.…”
Section: Loxl2 Induces Angiogenesis Independent Of Its Enzymatic Acmentioning
confidence: 98%
“…These data show that the effects of LOXL2 on EC migration and sprouting do not depend on LOXL2mediated enzymatic crosslinking of ECM components, but rather point toward a mechanism involving LOXL2-mediated intracellular signaling. 3.3 | LOXL2 is required but not sufficient to induce EndMT Given the known stimulatory effects of EndMT on angiogenesis (Muylaert et al, 2015;van Meeteren & ten Dijke, 2012) and the reported dominant role of LOXL2 in the regulation of EMT , we hypothesized that the observed results may be explained by a similar regulatory function of LOXL2 in EndMT.…”
Section: Loxl2 Induces Angiogenesis Independent Of Its Enzymatic Acmentioning
confidence: 98%
“…Traditionally it has been thought that the α-SM-actin expressing (SM)-like cells that accumulate in the above-mentioned vascular lesions were derived from proliferative expansion of resident vascular media SM cells (SMCs) or adventitial fibroblasts through the processes of de-differentiation of the former or differentiation of the latter. Through the years, however, this concept has been challenged by experimental data in not only the lung but also in the heart, kidney, and liver, demonstrating many possible sources of α-SM-actin expressing cells, including differentiation of resident vascular progenitor cells, recruitment of circulating progenitors or multi-functional inflammatory cells (fibrocytes), and finally the possibility that endothelial cells can transition into mesenchymal SM-like phenotype in a process recapitulating their developmental capabilities 2, 3 . Studies by Ranchoux et al 4 , and now by Hopper et al in this issue of Circulation 5 , provide convincing experimental evidence that endothelial-to-mesenchymal transition (EndMT) occurs in the setting of PAH/PH in both humans and animal models and potentially constitutes a target against which specific therapeutic agents could be utilized to abrogate the process and improve the status of the patient with PAH.…”
mentioning
confidence: 99%
“…As cells migrate away from the monolayer, their cortical cytoskeleton is rearranged to enable cell motility via developing actin-rich projections such as lamellipodia or filopodia. Loss of endothelial markers, such as vascular endothelial cadherin (VE-cadherin), platelet endothelial cell adhesion molecule (PECAM-1 or CD31), corresponds to loss of cell-cell adhesion, increased migration, and “de-differentiation” of the endothelial cell 2, 3, 7 . It is well described that as the cells move away from the monolayer and into an ECM rich environment, they develop the ability to not only produce but to remodel existing ECM.…”
mentioning
confidence: 99%
See 2 more Smart Citations